Partisipasi politik perempuan dalam kiprah dakwah partai keadilan sejahtera - Khadijah, Siti (The Journal of Religion and Communication Studies, 2024)
The purpose of this study is to analyze PKS's strategy to build women's political participation in its da'wah activities. The crisis of democracy is rationally caused by the lack of formal participation of the community, especially women in national politics. PKS has not maximized in utilizing alternative forms of women's participation through social media to fulfill affirmative policies. The efforts made by PKS have not been maximized in utilizing the strong influence of the media effects of the 4.0 era to increase women's political participation. The theoretical reference used is the theory proposed by Aeron Davis "Citizens, media effect and public participation" (Aeron Davis, 2019: 109-129). The concept of women's political participation in political parties can be brought closer to the term Ummah. This word is repeated 64 times in the word of Allah S.W.T, which is found among others in the 3rd surah (Ali-Imran) verse 110 and the 2nd surah (al-Baqarah) verse 143 and the 3rd surah (Ali-Imran) verse 110. Khyar means the best option, found in QS. As-Shaad [38]: 47. 'Aqibah which means impact or effect which in the Qur'an is mentioned 31 times of which is found in QS. Al-A'raf [7]: 128. This research paradigm is a critical paradigm using da'wah communication approaches, political communication, political parties and women's political participation. The research method consists of a type of research, namely descriptive qualitative. From this research, it can be seen that PKS encourages women to actively participate in politics as a manifestation of healthy democracy. Political awareness is built by conducting cadres every week through Ta'lim. The media used by PKS to build women's political participation is predominantly carried out through direct communication and is still minimal in the use of social media.